Phylogenetic analysis of Puumala virus strains from Central Europe highlights the need for a full-genome perspective on hantavirus evolution - Szabó, Róbert; Radosa, Lukáš; Ličková, Martina; Sláviková, Monika; Heroldová, Marta; Stanko, Michal; Pejčoch, Milan; Osterberg, Anja; Laenen, Lies; Schex, Susanne; Ulrich, Rainer G; Essbauer, Sandra; et al. (Virus genes, 2017)
Puumala virus (PUUV), carried by bank voles (Myodes glareolus), is the medically most important hantavirus in Central and Western Europe. In this study, a total of 523 bank voles (408 from Germany, 72 from Slovakia, and 43 from Czech Republic) collected between the years 2007-2012 were analyzed for the presence of hantavirus RNA. Partial PUUV genome segment sequences were obtained from 51 voles. Phylogenetic analyses of all three genome segments showed that the newfound strains cluster with other Central and Western European PUUV strains. The new sequences from Šumava (Bohemian Forest), Czech Republic, are most closely related to the strains from the neighboring Bavarian Forest, a known hantavirus disease outbreak region. Interestingly, the Slovak strains clustered with the sequences from Bohemian and Bavarian Forests only in the M but not S segment analyses. This well-supported topological incongruence suggests a segment reassortment event or, as we analyzed only partial sequences, homologous recombination. Our data highlight the necessity of sequencing all three hantavirus genome segments and of a broader bank vole screening not only in recognized endemic foci but also in regions with no reported human hantavirus disease cases.
Keywords: RNA, Viral; Myodes glareolus; RNA virová; Puumala orthohantavirus; Slovakia; Slovenská republika; Homologous recombination; Genotype; Orthohantavirus; fylogeneze; Česká republika; Phylogeny; Puumala virus; Europe; molekulární evoluce; Evolution, Molecular; Reassortment; Central Europe; Czech Republic; Evropa; Germany; Animals; Hantavirus Infections; lidé; Hantavirus; hantavirové infekce; Humans; zvířata; Německo; virus Puumala; Arvicolinae; genotyp